Smart Aquaculture Model for the Empowerment of Fisheries Micro, Small, and Medium Enterprises (MSMEs) through Digitalized Fish Farming Using an Automatic Feeding System - Agustina, Dian Resha; Defrizal, Defrizal; Dhora, Sony Tian; Sugandi, Mas Syntha Azzahra; Kushariantoko, A. Herbantolo Nurendro; Purmadya, M. Rafli; Syahputra, Muhammad Bintang (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2026)
Ornamental fish have become a popular hobby, offering beauty and tranquility to many homes. However, maintaining consistent feeding remains a challenge that often leads to malnutrition, stunted growth, and poor water quality due to overfeeding. This study aims to address these issues by developing an automatic fish feeding system integrated with Internet of Things (IoT) technology. The system employs an LDR sensor, DC motor, and NodeMCU ESP8266 microcontroller, enabling remote control and real-time monitoring through a mobile application connected to the Adafruit IO cloud. Using the experimental method, the system was tested for accuracy, connectivity, and feed timing performance. The results showed consistent feeding with an average delay of only three minutes, ensuring operational reliability. This research not only provides a practical solution for fish keepers but also supports digital empowerment for small-scale aquaculture businesses through the adoption of smart IoT systems.